Early Trabecular Development in Human Vertebrae: Overproduction, Constructive Regression, and Refinement - Acquaah, Frank; Robson Brown, Katharine A.; Ahmed, Farah; Jeffery, Nathan; Abel, Richard L. (Frontiers in Endocrinology, 2015)
Early bone development may have a significant impact upon bone health in adulthood. Bone mineral density (BMD) and bone mass are important determinants of adult bone strength. However several studies have shown that BMD and bone mass decrease after birth. If early development is important for strength why does this reduction occur? To investigate this more data characterising gestational, infant and childhood bone development are needed in order to compare with adults. The aim of this study is to document early vertebral trabecular bone development; a key fragility fracture site and infer whether this period is important for adult bone mass and structure. A series of 120 vertebrae aged between 6 months gestation to 2.5 years were visualised using micro-CT. Spherical volumes of interest were defined, thresholded and measured using 3D bone analysis software (BoneJ, Quant3D). The findings showed that gestation was characterised by increasing bone volume fraction whilst infancy was defined by significant bone loss (≈2/3rds) and the appearance of a highly anisotropic trabecular structure with a predominantly inferior-superior direction. Childhood development progressed via selective thickening of some trabeculae and the loss of others; maintaining bone volume whilst creating a more anisotropic structure. Overall the pattern of vertebral development is one of gestational overproduction followed by infant ‘sculpting’ of bone tissue during the first year of life (perhaps in order to regulate mineral homeostasis or to adapt to loading environment) and then subsequent refinement during early childhood. Comparison of early bone developmental data in this study with adult bone volume values taken from the literature shows that the loss in bone mass that occurs during the first year of life is never fully recovered. Early development could therefore be important for developing bone strength, but through structural changes in trabecular micro-architecture rather than bone mass.